2023
DOI: 10.1371/journal.pone.0283824
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of intestinal protozoa in young adults and their pets in Colombia, South America

Abstract: Intestinal parasitic infections have been considered a relevant public health problem due to the increased incidence worldwide. In developing countries, diarrhea and gastrointestinal symptoms cause impaired work capacity in adults and delayed rate growth in children. Enteric infections of unknown etiology can often lead to misdiagnosis, increased transmission, and morbidity. The aim of this study was to determine the prevalence of intestinal parasites in a young adult population and their pets. Stool samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Abdominal pain was the most consistently observed clinical manifestation among the symptomatic patients. Previous studies have similarly identified abdominal pain as the prevailing complaint among patients who have contracted the infection [ 31 , 32 , 54 ]. In contrast to asymptomatic patients, symptomatic patients who reported abdominal pain and diarrhea exhibited a greater prevalence of poly-parasitism [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain was the most consistently observed clinical manifestation among the symptomatic patients. Previous studies have similarly identified abdominal pain as the prevailing complaint among patients who have contracted the infection [ 31 , 32 , 54 ]. In contrast to asymptomatic patients, symptomatic patients who reported abdominal pain and diarrhea exhibited a greater prevalence of poly-parasitism [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…assemblages on dogs housed in a shelter and on their caretakers. Another study linked the transmission of GIP among university students to their infected pets [ 54 ]. This resulted from the fact that most Egyptians, particularly those who reside in the countryside, keep pets and domestic animals near their residences.…”
Section: Discussionmentioning
confidence: 99%